Quantificação e qualificação das estradas rurais na região geográfica imediata de Marechal Cândido Rondon - Lotte Júnior, Pedro Norberto (2023)
The objective of the research is to quantify and qualify the rural roads in the Immediate Region of Marechal Cândido Rondon. Nowadays, the vast majority of roads in Brazil are rural, with road transport being the main means of transportation, which presents inefficiencies in the terms of logistics. These roads play a fundamental role in the flow of agricultural production, in the receipt of inputs, and in the transportation of both goods and people. However, infrastructure defects such as potholes, corrugations, and wheel tracks are recurrent in these roads, causing delays, damages, and losses for the agricultural sector. Therefore, this research aims to determine the quantity of kilometers and qualify the rural roads in the Immediate Geographic Region of Marechal Cândido Rondon. The findings of this research provide relevant information for public officials and private initiatives, contributing to the improvement of transportation costs, the development of public policies, the creation of job opportunities, the promotion of tourism, and the improvement of the quality of life for the population. Moreover, with this knowledge, it is possible to identify critical points, reducing losses and environmental impacts. Thus, in order to determine the number of rural roads, interviews were conducted with secretaries and technicians responsible for them. As for qualification, Pitilin’s adapted methodology (2020) was used, with the necessary adjustments made, as well as the automatization of the entire repetitive and tiring process through information technology. In addition to generating this database, a map is generated using a geographic information system, enabling a better analysis of the origin of new transportation routes. With that, the results related to quantification revealed a total of 4,545.74 km of rural roads, of which 5% are excellent, 27% are good, 56% are average, 11% are poor, and 1% are very poor. Therefore, the majority of rural roads in this region are classified as average, indicating the need readjustment of these sections. Consequently, due to the lack of a database to analyze this information and a good methodology, disparities arise in the assessment of the conditions of rural roads. Thus, this research not only resulted in the creation of a database format with an objective and efficient methodology for these analyses, but also a new tool for the development of new routes, prioritization of critical points, search for places to stimulate tourism and ways to reduce losses in agricultural logistics, thus directly affecting regional development.